CATION SUBSTITUTIONS GOVERNING THE CHEMISTRY OF AMPHIBOLE IN THE SILGARÁ FORMATION METABASITES AT THE SOUTHWESTERN SANTANDER MASSIF - Rios, C.A (Boletín de Geología, 2010)
Amphibole-bearing parageneses from the Silgará Formation metabasites at the southwestern Santander Massif record evidence of prograding metamorphism. Optical and microprobe analyses, together with thermobarometric estimates on these rocks, show that the main variation in Ca-amphibole is the simultaneous substitution of Al into the T1 site (AlIV) and Na+K into the A-site of the amphibole’s crystal structure. AlIV is strongly temperature dependant, and this dependancy masks any pressure effect. Changes in the chemical composition of Ca-amphibole grains are interpreted through coupled substitutions, and reactions with co-existing minerals during an increase in metamorphic conditions from greenschist to lower amphibolite facies, being favourable circumstances record not only the metamorphic facies reached by rocks but also the P-T conditions by which these were attained. Keywords: amphibole, Silgará, metabasites, substitution, metamorphic conditions